2014
DOI: 10.1140/epje/i2014-14081-6
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble theory for slightly deformable granular matter

Abstract: Given a granular system of slightly deformable particles, it is possible to obtain different static and jammed packings subjected to the same macroscopic constraints. These microstates can be compared in a mathematical space defined by the components of the force-moment tensor (i.e. the product of the equivalent stress by the volume of the Voronoi cell). In order to explain the statistical distributions observed there, an athermal ensemble theory can be used. This work proposes a formalism (based on developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although it was originally developed for thermal systems, it can be applied to granular media. Several approaches [9,8,7,14,13,25] have been proposed since first Edward's model in 1989. That based on the extensive stress [14,13,25] has been followed in this research.…”
Section: Statistical Mechanics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was originally developed for thermal systems, it can be applied to granular media. Several approaches [9,8,7,14,13,25] have been proposed since first Edward's model in 1989. That based on the extensive stress [14,13,25] has been followed in this research.…”
Section: Statistical Mechanics Approachesmentioning
confidence: 99%
“…Several approaches [9,8,7,14,13,25] have been proposed since first Edward's model in 1989. That based on the extensive stress [14,13,25] has been followed in this research.…”
Section: Statistical Mechanics Approachesmentioning
confidence: 99%
“…al. [48] pointed out that the size of the time step in DEM simulations may influence the width and the shape (but not the mean) of the determined probability distributions, even if the time step appears sufficiently small using common criteria. In order to make sure that this effect does not influence our results, we repeated some of the simulations with a time step of ∆t = 10 −5 s. We found that the mean volume fraction, the volume fraction variance and also the shape of the volume fraction distribution did not change on reduction of the time step.…”
Section: Excitation Protocols and Parametersmentioning
confidence: 99%